Design and Comparative Analysis of the REV Team Electric Car Chassis with Material Variations Using FEM - Ahmad Zahrul Firdaus; Marsono Marsono (Universitas Sultan Ageng Tirtayasa, 2026)
The demand for high-performance and energy-efficient electric vehicles in competitions such as the Kompetisi Mobil Listrik Indonesia (KMLI) and Formula SAE necessitates chassis designs that are lightweight, rigid, and safe. This study aims to optimize chassis performance through a comparative analysis of Aluminum A6061-T4, Aluminum A6061-T6, and AISI 4130 using the Finite Element Method (FEM). The research method has several main stages, with FEM process included pre-processing, solution, and post-processing. A 3D chassis was modeled in SolidWorks 2023 and simulated in ANSYS 2024 R1 under static loading. Results show that A6061-T6 provides the best performance with 0.528 mm deformation and a safety factor of 6.114. In addition, mass calculation shows that aluminum chassis (14.967 kg) is significantly lighter than AISI 4130 (43.514 kg), achieving a weight reduction of approximately 65.6%. The findings suggest that A6061-T6 offers an optimal combination of lightweight properties and structural integrity for competition electric vehicle chassis.